2014
DOI: 10.1089/acm.2014.0061
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Horseback Riding in Breast Cancer Survivors: A Pilot Study

Abstract: EAT had positive effects on both physiologic and psychological measures, enhancing quality of life of breast cancer survivors. RESULTS suggest a new method for rehabilitation intervention strategies after cancer in a nonmedical environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
77
0
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(85 citation statements)
references
References 24 publications
0
77
0
8
Order By: Relevance
“…For example, establishing rapport with the horse and mastering riding can improve a host of benefits such as increases in self-esteem, confidence, and accomplishment. Similarly, one of the first controlled studies on the effects of horseback riding on breast cancer survivors [49] showed that the treatment group experienced significant improvements on numerous aspects of aerobic capacity, strength, and quality of life. Collectively, the above better-controlled studies more forcefully argue that AAT may be more therapeutic than no-AAT controls for a wide variety of conditions such as negative symptoms of mental illness, ADHD, and dementia, as well as overall quality of life for stroke and breast cancer survivors.…”
Section: Randomized Control Group Field Studiesmentioning
confidence: 93%
“…For example, establishing rapport with the horse and mastering riding can improve a host of benefits such as increases in self-esteem, confidence, and accomplishment. Similarly, one of the first controlled studies on the effects of horseback riding on breast cancer survivors [49] showed that the treatment group experienced significant improvements on numerous aspects of aerobic capacity, strength, and quality of life. Collectively, the above better-controlled studies more forcefully argue that AAT may be more therapeutic than no-AAT controls for a wide variety of conditions such as negative symptoms of mental illness, ADHD, and dementia, as well as overall quality of life for stroke and breast cancer survivors.…”
Section: Randomized Control Group Field Studiesmentioning
confidence: 93%
“…Es können nur wenige Studien zur Wirksamkeit des therapeutischen Reitens bei krebskranken Kindern gefunden werden. Rudo (2009) [23]. Trotz dieser allgemeinen Empfehlungen orientieren sich die Inhalte der Reittherapie an der Schadensform, dem Gesundheitszustand, der Tagesform und der Reiterfahrung der Patienten [24].…”
Section: Erkenntnisse Zum Therapeutischen Reiten In Der Onkologieunclassified
“…[20 -23]. So konnten beispielsweise die Ausdauerleistungsfähigkeit und Muskelkraft [20,23], koordinative Fähigkeiten [20,21] charakter der Pferde bereits ein wesentliches Argument für das therapeutische Reiten in der Onkologie, insbesondere für krebskranke Kinder. Dadurch kann die Motivation der teilweise "therapiemüden" Patienten gesteigert werden, wodurch eine langfristig gute Compliance in der Therapie wahrscheinlicher werden könnte.…”
Section: Erkenntnisse Zum Therapeutischen Reiten In Der Onkologieunclassified
See 2 more Smart Citations